Clinical Governance and Healthcare Quality: A Systematic Review of Global Implementation and Organizational Challenges - Siregar, Erihka Silvia; Imtiyaaz, Siti Luluiyah; Ardi, Ardi; Sunarjo, Richard A.; Wuisan, Dewi Sri Surya (Journal of Cultural Analysis and Social Change, 2025)
This article critically examines the process, practical challenges, and possible effects of clinical governance on patient safety and quality of service delivery within different health systems. Background Problems: On the contrary, countries with middle and low income have a number of challenges, including inadequate accountability systems, inadequate professional education, and insufficient resources. The research purports that clinical governance has become an elaborate management framework, which combines elements of the safety culture, clinical audit, risk management, and clinical leadership within the healthcare industry. Value-based governance and digital systems such as AI-based quality control monitoring are more popular in countries that have more developed medical systems. Research Methods: They were found in the Talk about A systematic literature review of 44 articles published between 2000 and 2025, thematic focus content in the study was organized into three categories: programming (45%), struggles (32%), and impact on the patient safety and service quality (23%). Finding/Results: However, a number of studies indicate that successful implementation of clinical governance is positively linked with the enhancement in quality of services, organizational performance, and patient confidence in healthcare organizations. Overall, the above findings indicate that clinical governance is a manifestation of an organizational culture whereby the value of patient safety is highly prioritized and that it is not merely a policy instrument. The ideas suggested in this study to enhance clinical leadership capacity, digitalize quality audits, and localize policies are suggested as a viable strategy toward a more transparent, effective, and equitable health system.